Loyalitas Karyawan dan Budaya Organisasi pada Perusahaan - Christi, Aland Julio; Sridadi, Ahmad Rizki (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2022)
The purpose of this study was to determine the effect of organizational culture on employee loyalty through job satisfaction and quality of work life on CV. Sinar Ban. This research is interesting to study because the work done by employees is the same job continuously every day, whether this makes employee loyalty high or low. With the number of respondents as many as 45 people which is the total of the entire population. This study used quantitative methods and analyzed using Partial Least Square - Structural Equation Modeling. From this study, it was found that organizational culture had a significant positive effect on employee loyalty, organizational culture had a significant positive effect on job satisfaction, and organizational culture had a significant positive effect on the quality of work life. Then job satisfaction and quality of work life have a significant positive effect on employee loyalty. Then job satisfaction and quality of work life have a significant effect on partial mediation between the influence of organizational culture on employee loyalty.